Hungarian Monitoring, 1 March 1989 . [Magyar rádiófigyelő], 1989. március 1 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - New draft constitution made public in Lithuania - Reports on the Rushdie affair - Armenian commemorations of Sumgait - Pravda article sharply criticizes Latvian debates - Nationality problems in Slovenia - Unilateral GDR armed force reductions Domestic Affairs: - Hungarian Social Democratic Party's debate on principles - Hungarian Socialist Workers' Party (MSZMP) and March Front think it is still too early to announce elections - Rezső Nyers and István Huszár receive European Parliamentary delegation in Budapest - Political Committee meeting yesterday discussed concepts of discussing the army and situation of the border guards Economy: - Hungarian Socialist Workers' Party (MSZMP) economic policy sub-committee prepares summary statement on Hungarian economy over the past 4 years - Chamber of Commerce also discusses economic management and possibilities for an economic turn - From today, domestic trade banks will also deal with companies' currency exchange affairs - Skála store with foreign exchange opens in Tatabánya Külpolitika: - Litvániában új alkotmánytervezetet hoztak nyilvánosságra - A Rushdie üggyel kapcsolatos beszámolók - Örményországi megemlékezés a szungajti eseményekről - Éles PRAVDA cikk a lettországi viták ügyében - Nemzetiségi problémák Szlovéniában - Egyoldalú NDK haderőcsökkentés Belpolitika: - A MSZDP elvi nyilatkozata - Az MSZMP és a Márciusi Front szerint még korai lenne a választások kiírása - A Budapesten tartózkodó Európa Parlament küldöttségét fogadta NYERS R. és HUSZÁR István - A PB tegnapi ülésén a néphadsereg-fejlesztési koncepcióról és a határőrség helyzetéről is szó volt Gazdaság: - Az MSZMP gazdaságpolitikai albizottsága elkészítette összefoglaló jelentését a magyar gazdáság elmúlt 4 évtizedéről - Magyar Gazdasági Kamrában is megvitatták a gazdaságirányítás 58 és a gazdasági fordulat lehetőségeit - Mától a hazai kereskedelmi bankok is foglalkoznak a vállalatok 61 deviza ügyeivel - Devizáért árusító SKÁLA nyílik Tatabányán